"More than just a library": Public libraries in the 'smart city'. (December 2018) - Leorke, Dale; Wyatt, Danielle; McQuire, Scott
Abstract: This paper argues that the transformation of the contemporary public library can be usefully understood by situating it within the context of the technology-driven urban vision of the 'smart city'. We explore this through a focus on a recent public library development in Australia where a high-profile new library features as a signature investment in the city's broader digital and 'smart city' strategies. In analysing the library's entanglement with the digital visions of this city, our case study reveals the uneven and often contradictory impacts that characterize the digital economy. We argue that the articulation of a technology-led agenda with neoliberal governance settings has produced institutional tensions that go to the core of the library's role in public life, challenging us to consider how libraries might best serve a range of rapidly changing and competing needs and publics. We find that while libraries have been forced to make certain changes, they have also developed proactive responses to new technology. Efforts to reinvent themselves as 'hubs', 'makerspaces' and co-located community centres offering enriched spaces for social gathering, targeted learning, and new forms of creative production, including entrepreneurial activity and innovation, are strategies for maintaining and extending the traditional remit of the public library. However, these transformations are not adequately recognised within the structures through which libraries are evaluated and funded, thus making them vulnerable to future governmental agendas.